Postnatal Oral Glucose Tolerance Test in Normoglycemic Women Delivering Macrosomic Babies (Medical Forum Monthly, 2021)
Objective: To determine the frequency of diabetes by oral glucose tolerance test (OGTT) among normoglycemic women delivering macrosomic babies.Study Design: Observation study.Place and Duration of Study: This study was conducted at the MCH Unit II, Pakistan Institute of Medical Sciences, Islamabad from May 2015 to April 2017.Materials and Methods: 100 normoglycemic woman with BMI of 19-25 Kg/m2 and singleton pregnancy at 37-40 weeks of gestation who delivered macrosomic babies >4kg were included. Patients with twin pregnancy, type II diabetes, gestational diabetes and medical diseases were excluded. All OGTTs were performed after 24 hours of delivery and then six weeks postpartum in the morning after an overnight fast. Blood plasma glucose levels above 5.6mmol/l, fasting and 7.8 mmol/L (140 mg/dl) at 2 hours were categorized as diabetes.Results: The mean age of total 100 women was 29.9 years and the mean gestational age was found 38. 6 weeks. The mean of birth weight was 4.48 (n=100). After 24 hours, diabetes was diagnosed by OGTT in 40 (40.0%) woman but there was no diabetes in 60 (60.0%) patients (total n=100). At 6 weeks diabetes was found in 27 (27.0%) woman who delivered macrosomic babies, whereas there was no diabetes in 73 (73.0%) patients.Conclusion: Frequency of diabetes diagnosed by oral glucose tolerance test (OGTT) among normoglycemic women delivering macrosomic babies is high.